The legal framing of false news about "Covid 19" in Algeria : between the responsibility of the media law and the penal code - Djaballah, Hakima; Meribai, Ismahane (Journal of Human Sciences, 2021)
The subject of false news is one of the problems that has been exacerbated in this era, especially with the emergence of the Covid19 crisis, which has opened the way for its spread, with technological development and the availability of digital communication mechanisms. Algeria, like other countries, is exposed to a huge amount of false news about the coronavirus, so we will try through this article to find out the place of false news in the organic law of media, audiovisual law and penal code. We will use the descriptive approach to the problems of the ego and will use the observation and the studies available in this field. One of important results is the need to update the media laws and penal code in accordance time, as well as the strict application of them and the need to pay attention to professional ethics, especially digital media education.